Fluid Fields : The Un/Making of the Research Field in Transdisciplinary Knowledge Co-Production - Gruber, Valerie (2021)
The quest for transdisciplinary research requires academics to collaborate with actors from heterogeneous fields, both inside and outside academia. In order to transcend disciplinary, social, symbolic or physical boundaries, co-producers of knowledge need to deal with multiple relations, theories and practices taken for granted in each field involved. This presentation explores how field alignments can be made between researchers, artists and activists in order to create synergies and produce knowledge collaboratively. It draws on a participatory research project developed with diverse actors from Brazil, Colombia, Mozambique, Cameroon and Germany, who share a common interest in understanding whether and how the arts can contribute to processes of transformation in communities afflicted by violence, racism and social exclusion. The reflection shows how the research field emerges as a fluid third space co-created by actors with specific knowledges and positionalities. Ultimately, this presentation raises fundamental questions on whose queries, assumptions, interests, theories and methodologies count as legitimate, giving them the power to (re)define a research field.